Ideas for the classroom (Journal of Parents and Teachers, 2014)
In order to learn more about planetary surfaces and planetary satellites, this didactic card suggests creating a planetary diorama with very simple material such as sand, cardboard and plasticine. In addition two more experiments are suggested: first one is building a photometer to measure light and the other one is to simulate measuring the distance between stars.
Keywords: ideas; class activity; didactics; astronomy; didactic resources.